2019
DOI: 10.1002/smtd.201800480
|View full text |Cite
|
Sign up to set email alerts
|

1 + 1′ > 2: Heteronuclear Biatom Catalyst Outperforms Its Homonuclear Counterparts for CO Oxidation

Abstract: By means of density functional theory (DFT) computations, the CO/O2 adsorption and CO oxidation pathways on the biatom catalyst, namely the heteronuclear Fe1Cu1@C2N, in comparison with its homonuclear counterparts Fe2@C2N and Cu2@C2N are systemically investigated. The reactions of O2 dissociation and CO oxidization with preadsorbed CO or O2 are comparably studied. The computations find that the heteronuclear species Fe1Cu1@C2N possesses high stabilities and is feasible to be synthesized experimentally. More im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 80 publications
(111 reference statements)
1
64
0
Order By: Relevance
“…41 Particularly, the 0.83 nm sized holes terminated by sp 2 -bonded nitrogen atoms provide the conditions for anchoring two transition-metal atoms, which offers the opportunity for construction of multiple active sites. 42,43 Alloying different metal species is a general strategy to achieve multiple active sites tuning the binding strength of the targeted intermediates. [42][43][44][45] With regard to the CO 2 RR, in order to reduce the high free energy change of the potential determining step (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Particularly, the 0.83 nm sized holes terminated by sp 2 -bonded nitrogen atoms provide the conditions for anchoring two transition-metal atoms, which offers the opportunity for construction of multiple active sites. 42,43 Alloying different metal species is a general strategy to achieve multiple active sites tuning the binding strength of the targeted intermediates. [42][43][44][45] With regard to the CO 2 RR, in order to reduce the high free energy change of the potential determining step (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 Alloying different metal species is a general strategy to achieve multiple active sites tuning the binding strength of the targeted intermediates. [42][43][44][45] With regard to the CO 2 RR, in order to reduce the high free energy change of the potential determining step (Fig. 1a), additional O-binding sites are required to stabilize the oxygen-containing intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the electrocatalytic reactions mentioned above, SACs have also been reported to be used in other catalytic reactions, including NRR, [105,148] WGSR, [106,149,150] methane reforming, [111,151,152] methanol steam reforming, [153] CO oxidation, [22,52,[154][155][156] benzene oxidation, [58] acetylene hydrogenation, [96] and so on. Shan et al [111] reported an atomically dispersed Rh on the zeolite (Rh/ZSM-5) catalyst, which can convert methane into methanol or acetic acid in liquid phase mild oxidation at 150 °C.…”
Section: Other Catalytic Applicationsmentioning
confidence: 99%
“…The metal atoms can be homonuclear [115,157,158] or heteronuclear. [154,159,160] Experimental measurements [56,61,67,121,161] and density functional theory (DFT) calculations [162,163] showed that the dimer or trimer catalyst could achieve attractive catalytic performance, even better than that of SACs (Figure 10), especially the heteronuclear dimer atom catalyst. Although the synthesis of dimer or trimer atoms catalysts is not yet mature, the recently reports showed excellent catalytic performance of dimer or trimer atoms catalysts, suggesting their great potential for certain applications.…”
Section: ) Detection Of the Mechanism Of Sacs For Different Reactionsmentioning
confidence: 99%
“…S2 †). The lowest activation energy of O 2 decomposition is 0.854 eV (MnN 2 C 2 -opp) among the three structures, the CO oxidation process is difficult to perform at room temperature when the energy barrier is greater than 0.8 eV, 43 this means that the kinetics are not conducive to O 2 dissociation and O 2 adsorbed on MnN 2 C 2 can be effectively activated without decomposition at room temperature. Aer adsorbing O 2 , there will be three cases of CO adsorption.…”
Section: Reaction Mechanism Of Co Oxidation On Mnn 2 Cmentioning
confidence: 98%